Analisis Model Predator-Prey Tanaman Lada, Hama Penggerek Batang, dan Penghisap Buah - M. Diwa Sandika Aditama; Dear Michiko Mutiara Noor; Nela Rizka (Mathematical Sciences and Applications Journal, 2024)
Pepper (Piper nigrum L.) is one of the oldest and most popular spices in the world and one of the important plantation crops in Indonesia, especially in Lampung Province. In cultivating pepper plants, many farmers are faced with the problem of pest attacks so that the productivity of pepper plants decreases due to pest attacks. Pests that attack pepper plants in Lampung Province include stem borers and fruit suckers. This research was conducted to look at the predator-prey mathematical model between pepper plants and stem borer and fruit sucking pests and to see the effect of pesticide control on this phenomenon. Modeling was carried out using the Holling II function. The results of numerical simulations on the predator-prey model without control show that the model will be stable in conditions where there is a population of pepper plants, while the populations of stem borers and fruit suckers experience extinction. However, if the parameter values \[ \gamma \] > 0.001045 and \[ \delta \] > 0.008032, then the model will not be stable under these conditions. Furthermore, the simulation shows that the use the use of pesticide control can accelerate the reduction in pest growth.